Cutaneous, gastrointestinal, hepatic, endocrine, and renal side-effects of anti-PD-1 therapy - Hofmann, Lars; Forschner, Andrea; Loquai, Carmen; Goldinger, Simone M.; Zimmer, Lisa; Ugurel, Selma; Schmidgen, Maria I.; Gutzmer, Ralf; Utikal, Jochen S.; Goeppner, Daniela; Hassel, Jessica C.; Meier, Friedegund; et al. (European Journal of Cancer, 2016)
Anti-programmed cell death receptor-1 (PD-1) antibodies represent an effective treatment option for metastatic melanoma as well as for other cancer entities. They act via blockade of the PD-1 receptor, an inhibitor of the T-cell effector mechanisms that limit immune responses against tumours. As reported for ipilimumab, the anti-PD-1 antibodies pembrolizumab and nivolumab can induce immune-related adverse events (irAEs). These side-effects affect skin, gastrointestinal tract, liver, endocrine system and other organ systems. Since life-threatening and fatal irAEs have been reported, adequate diagnosis and management are essential.In total, 496 patients with metastatic melanoma from 15 skin cancer centers were treated with pembrolizumab or nivolumab; 242 side-effects were described in 138 patients. In 116 of the 138 patients, side-effects affected the skin, gastrointestinal tract, liver, endocrine, and renal system. Rare side-effects included diabetes mellitus, lichen planus, and pancreas insufficiency due to pancreatitis.Anti-PD1 antibodies can induce a plethora of irAEs. The knowledge of them will allow prompt diagnosis and improve the management resulting in decreased morbidity.
EVALuna2:19570

Morphologische Kriterien vesikulobullöser Hauterkrankungen in der konfokalen In-vivo-Laserscanmikroskopie - Samhaber, Kinga T.; Buhl, Timo; Brauns, Birka; Hofmann, Lars; Mitteldorf, Christina; Seitz, Cornelia S.; Schoen, Michael P.; Rosenbergers, Albert; Haenssle, Holger A. (Journal der Deutschen Dermatologischen Gesellschaft, 2016)
Konfokale Laserscanmikroskopie (Reflectance confocal microscopy; RCM) kann eine nützliche Methode für die genaue, schnelle und nicht-invasive Diagnose für vesikullobullöse Hauterkrankungen (VSD) am Krankenbett sein. Das primäre Ergebnis dieser Studie war eine deskriptive statistische Analyse von RCM-Merkmalen, die mit einer ausgewählten Gruppe an VSD einhergehen.Monozentrische Beobachtungsstudie an einer Universitätsklinik für Dermatologie. Vierzig Hautläsionen bei 24 Patienten mit bullösem Pemphigoid (BP), Infektion mit Varizella Zoster (VZI) oder allergischer Kontaktdermatitis (ACD) wurden ausgewertet.Patienten mit BP, VZI und ACD wurden auf die Anwesenheit eines großen Spektrums an RCM-Merkmalen hin untersucht, darunter die histopathologische Korrelation von Spongiose, Vesikel/Hautblasen, epidermaler Nekrose, pleomorphen, ballonierte Keratinozyten und entzündlichen Infiltraten. Die drei Erkrankungen zeigten spezifische Muster für Auftreten dieser RCM-Merkmale. Wir identifizierten mit Hilfe einer multivariaten Regressionsanalyse einen Satz morphologischer Merkmale bei BP (Vesikel/Hautblasen an der dermoepidermalen Junktionszone, entzündliche Infiltrate in Hautblasen und basalen Epidermisschichten, Spongiose in basalen Epidermisschichten), VZI (Akantholyse im Stratum spinosum, epidermale Nekrose, pleomorphe, ballonierte Keratinozyten, multinukleäre Riesenzellen) und ACD (Mikrovesikel, Spongiose und auffällige entzündliche Infiltrate im Stratum granulosum/spinosum).RCM scheint ein nützliches Werkzeug bei der Analyse und der Unterscheidung einer ausgewählten Gruppe von VSDs zu sein und bietet eine gute Korrelation mit histopathologischen Untersuchungsergebnissen.
EVALuna2:19620

Neurological, respiratory, musculoskeletal, cardiac and ocular side-effects of anti-PD-1 therapy - Zimmer, Lisa; Goldinger, Simone M.; Hofmann, Lars; Loquai, Carmen; Ugurel, Selma; Thomas, Ioannis; Schmidgen, Maria I.; Gutzmer, Ralf; Utikal, Jochen S.; Goeppner, Daniela; Hassel, Jessica C.; Meier, Friedegund; et al. (European Journal of Cancer, 2016)
Anti-programmed cell death 1 (PD-1) antibodies represent an effective treatment option for metastatic melanoma and other cancer entities. They act via blockade of the PD-1 receptor, an inhibitor of the T-cell effector mechanisms that limit immune responses against tumours. As reported for ipilimumab, the anti-PD-1 antibodies pembrolizumab and nivolumab can induce immune-related adverse events (irAEs). These side-effects can involve skin, gastrointestinal tract, liver, the endocrine system and other organ systems. Since life-threatening and fatal irAEs have been reported, adequate diagnosis and management are essential.In total, 496 patients with metastatic melanoma from 15 skin cancer centres were treated with pembrolizumab or nivolumab. Two hundred forty two side-effects in 138 patients have been analysed. In 77 of the 138 patients side-effects affected the nervous system, respiratory tract, musculoskeletal system, heart, blood and eyes. Not yet reported side-effects such as meningo-(radiculitis), polyradiculitis, cardiac arrhythmia, asystolia, and paresis have been observed. Rare and difficult to manage side-effects such as myasthenia gravis are described in detail.Anti-PD-1 antibodies can induce a plethora of irAEs. The knowledge of them will allow prompt diagnosis and improve the management resulting in decreased morbidity.
EVALuna2:19571